2007
DOI: 10.1111/j.1365-2761.2007.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to soy: T‐cell‐like reactivity in the intestine of Atlantic salmon, Salmo salar L.

Abstract: T-cell-mediated hypersensitivity could be central in soybean meal (SBM)-induced intestinal changes in salmon. However, tools for immunohistochemical detection of T cells have been lacking in teleosts, including Atlantic salmon. Application of a specific histochemical protocol allowed demonstration of T-cell-like reactivities in formalin-fixed, paraffin-embedded tissues using an antibody reacting to a conserved region of human CD3epsilon (Dako A0452). Characteristic staining was observed in cells of the thymus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 30 publications
11
74
3
1
Order By: Relevance
“…This is in agreement with past reports showing upregulation of CD4-1 transcripts in lymphoid organs of salmon and trout in response to immunogenic stimuli (16,(48)(49)(50)(51)(52)(53)(54), usually interpreted as an indicator of CD4 + T cell proliferation. Proliferation also has been reported for CD4-1 + cells isolated from ginbuna carp during allogeneic MLR as well as after Ag-specific stimulation (18).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with past reports showing upregulation of CD4-1 transcripts in lymphoid organs of salmon and trout in response to immunogenic stimuli (16,(48)(49)(50)(51)(52)(53)(54), usually interpreted as an indicator of CD4 + T cell proliferation. Proliferation also has been reported for CD4-1 + cells isolated from ginbuna carp during allogeneic MLR as well as after Ag-specific stimulation (18).…”
Section: Discussionsupporting
confidence: 93%
“…The former assays were performed as described by Bakke-McKellep et al (2007) for PCNA and Sanden et al (2005) for caspase-3, using a mouse anti-PCNA (Santa Cruz Biotechnology) and cleaved caspase-3 antibody (Cell Signalling), respectively. Sections incubated with normal fish serum instead of the primary antibody or without substrate incubation were used as negative controls.…”
Section: Histological Histochemical and Immunohistochemical Proceduresmentioning
confidence: 99%
“…In salmonids, inflammation of the distal intestine (van den Ingh et al, 1991;Rumsey et al, 1994;Baeverfjord and Krogdahl, 1996) and ulcer-like lesions in the stomach (Refstie et al, 2006a)c a u s e d by antinutritional factors in the plant protein has presented problems such as reduced intestinal absorptive ability and increased disease susceptibility Bakke-McKellep et al, 2007a). Proliferation of distal intestine enterocytes of SBM-fed Atlantic salmon, Salmo salar was observed using antibodies against PCNA (Sanden et al, 2005) and changes in trypsin activity and gene expression have also been observed in both Atlantic salmon (Krogdahl et al, 2003;Lilleeng et al, 2007b) and rainbow trout, Oncorhynchus mykiss (Romarheim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%